2020
DOI: 10.1001/jama.2020.4437
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Initiation of Pulmonary Rehabilitation After Hospitalization for COPD and 1-Year Survival Among Medicare Beneficiaries

Abstract: IMPORTANCE Meta-analyses have suggested that initiating pulmonary rehabilitation after an exacerbation of chronic obstructive pulmonary disease (COPD) was associated with improved survival, although the number of patients studied was small and heterogeneity was high. Current guidelines recommend that patients enroll in pulmonary rehabilitation after hospital discharge. OBJECTIVE To determine the association between the initiation of pulmonary rehabilitation within 90 days of hospital discharge and 1-year survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
133
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 34 publications
2
133
1
6
Order By: Relevance
“…Likely, a fraction of patients not mechanically ventilated (also including patients on high-flow oxygen therapy) will need to be added, as some of these still have significant functional consequences of the hospital admission (Belli et al Under review ERJ; Paneroni et al Under review ERJ) . We strongly encourage countries to take action to organise rehabilitation for this influx of patients, on top of the many patients with chronic respiratory disease who already qualify for pulmonary rehabilitation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likely, a fraction of patients not mechanically ventilated (also including patients on high-flow oxygen therapy) will need to be added, as some of these still have significant functional consequences of the hospital admission (Belli et al Under review ERJ; Paneroni et al Under review ERJ) . We strongly encourage countries to take action to organise rehabilitation for this influx of patients, on top of the many patients with chronic respiratory disease who already qualify for pulmonary rehabilitation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary rehabilitation provides exercise training and education to improve the physical and psychological condition of individuals with chronic respiratory diseases [66,67]. While the strongest data exist for patients with COPD [68], pulmonary rehabilitation is also beneficial in other chronic respiratory conditions [69], including survivors of critical illness due to viral pneumonias [70][71][72]. Early experience with pulmonary rehabilitation in COVID-19 survivors from China indicates that a 6-week pulmonary rehabilitation programme can improve pulmonary function, quality of life measures and anxiety [73], although additional research is needed [73][74][75][76].…”
Section: Physical Outcomesmentioning
confidence: 99%
“…Though there is limited data on the effects of early rehabilitation in COVID-19, recent studies on patients admitted with chronic lung disease showed that early pulmonary rehabilitation improved one year mortality rates. 15 Strategy 7: Use an Evidence-Based Approach to Prescribing Therapeutic Modalities…”
Section: Strategy 6: Encourage Early Mobilization and Rehabilitationmentioning
confidence: 99%